2019
DOI: 10.3390/nano9050663
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Boundary Characteristics of Homo-/Heterogeneous Interfaces

Abstract: The interface of two solids in contact introduces a thermal boundary resistance (TBR), which is challenging to measure from experiments. Besides, if the interface is reactive, it can form an intermediate recrystallized or amorphous region, and extra influencing phenomena are introduced. Reactive force field Molecular Dynamics (ReaxFF MD) is used to study these interfacial phenomena at the (non-)reactive interface. The non-reactive interfaces are compared using a phenomenological theory (PT), predicting the tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In our previous studies [26,35] on Pt and Ni systems, we observed that the thermal conductivity scales with the length of the simulated molecular system. SS-NEMD simulations of different system sizes of Pt and Ni are required to extrapolate to the infinite size thermal conductivities, which is equal to the theoretical thermal conductivity of a bulk material.…”
Section: Length Dependent Thermal Conductivitymentioning
confidence: 75%
See 1 more Smart Citation
“…In our previous studies [26,35] on Pt and Ni systems, we observed that the thermal conductivity scales with the length of the simulated molecular system. SS-NEMD simulations of different system sizes of Pt and Ni are required to extrapolate to the infinite size thermal conductivities, which is equal to the theoretical thermal conductivity of a bulk material.…”
Section: Length Dependent Thermal Conductivitymentioning
confidence: 75%
“…Steady-state Non-Equilibrium Molecular Dynamics (SS-NEMD) simulations using the reactive force field are performed to calculate the thermal conductivity of MgCl 2 • nH 2 O (n = 0, 1, 2, 4 and 6), and CaCl 2 • 2H 2 O. This is an often used MD method to compute the thermal conductivity [25][26][27][28] . The size of the cross-sectional area and length of the system along the heat flow direction affect the thermal conductivity at a molecular level [27,28] .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Numerous classical force fields have been developed, e.g., TIP4P/2005 18 for H 2 O and TraPPE 19 for CO 2 . By using such a force field, important properties such as the adsorption and diffusion of fluids in porous media 11,12,20 and thermal behavior 11,21 of materials can be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an important requirement for molecular studies of fluids in porous media is the correct description of the vapor–liquid equilibrium (VLE) by the force field. , Numerous classical force fields have been developed, e.g., TIP4P/2005 for H 2 O and TraPPE for CO 2 . By using such a force field, important properties such as the adsorption and diffusion of fluids in porous media ,, and thermal behavior , of materials can be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, there is a paper describing a study of the thermal boundary characteristics of homo-and heterogeneous, reactive, and nonreactive interfaces between two solids by Heijmans et al [3]. Via a connection between reactive force field molecular dynamics and phenomenological theory, a continuous temperature profile was found for the homogeneous nonreactive interface, while a temperature jump was found for the heterogeneous nonreactive interface.…”
mentioning
confidence: 99%